Hydrological and Geomorphological Observations on a High Latitude Drainage Basin: "Jason's Creek", Devon Island, N.W.T. - Cogley, John Graham (My University, 1971)
"Jason's Creek" is a stream draining 2.2 km^2 of arctic limestone terrain. Its annual regime consists of a ten-month period in which it is frozen to its bed, a short spring flood which occurs shortly after tenperatures cross the freezing-point in late June, and a period of about two months during which discharge is relatively low and fluctuates diurnally in response to inputs of radiative and heat energy to the snowpack. In 1970, the spring flood occupied the first two weeks of July and effected the discharge of some nine-tenths of total annual runoff. Tne low flow period was punctuated by rainstorms which generated sharply-defined floods: basin response was rapid and efficient, for storm runoff is facilitated over the unvegetated ground and through the shallow active layer above the permafrost table. Covariance and spectral analyses suggest a basin lag time of five hours, both for low discharges of snowmelt water and flood discharge of rainwater. It appears, from the spectra of the time series, that radiation is a better index of snowmelt discharge than is temperature.
Most of the annual removal of sediment from the basin takes place during the spring flood, when the stream is turbid and movement of channel bed material is vigorous, In the longer period after the flood the main component of stream load is the solute load. The concentration of dissolved material varies inversely while suspended sediment concentration varies directly with discharge. Solute concentrations are lower than those commonly found in limestone streams at lower latitudes, suggesting that in "Jason's Creek" the increased solubility of CO2 at low temperatures is more than counteracted by a decrease in the rate of solution of CaCO3. There are also indications that the concentration of CO2 in snowmelt water 2 may be smaller, in absolute terms, than in rainwater.
The role of water is crucial in many processes acting on slopes and delivering detritus to stream channels; rills, for example, remove ions in solution and fine particles in suspension, notably from the base of talus slopes, and lubrication of the active layer after rainstorms generates bowl-slide and mudflow activity.
Keywords: "Jason's Creek", hydrological, high latitude, drainage, basin, layer, channel